Sustainable Treatment of Palm Oil Mill Effluent (POME) by using Pectin and Chitosan in Jar Test Protocol – Sequential Comparison - Kamaruddin, Mohamad Anuar; Ismail, Norli; Kuen, Tan Hwee; Alrozi, Rasyidah (International Journal of Integrated Engineering, 2019)
Oil palm industry in Malaysia is developing as demand towards alternative and cheaper edible oil continuously received from the European Union. However, adverse environmental impacts from this activity coupled with laden recalcitrant effluent contribute to the water pollution pose risk to water body and human’s health. The purpose of this research project is to compare the efficiency between Pectin (Heteropolysaccharide) and Chitosan (D-glucosamine) for tertiary treatment of anaerobic-aerobic treated palm oil mill effluent (POME). Factor that affecting the efficiency of the coagulation process such as dosage of coagulant used was studied by using jar-test protocol. From the experimental results, the ideal experimental conditions that remove turbidity, COD and colour were exceptional when using Chitosan. At this condition 83% of turbidity, 88% of TSS, 79% of colour and 53.1% of COD were removed. Nevertheless, it was observed that pH plays dominating factor that contribute to the overall removal efficiency. This research would give an idea on alternative way for tertiary wastewater treatment of POME.